Chronic postoperative pain: ubiquitous and scarcely appraised: narrative review - Lopes, Alexandre [UNESP]; Menezes, Miriam Seligman; Barros, Guilherme Antonio Moreira De [UNESP] (Sociedade Brasileira de Anestesiologia (SBA), 2021)
The International Association for the Study of Pain chose pain prevention as the theme for the 2020 Global Year. Chronic postoperative pain is one the many types of pain that can be potentially prevented. It develops or increases in severity after a surgery, persists for at least three months, even after ruling out all other possible causes of pain. To perform the present narrative review, the authors searched the PubMed database using the following keywords “postoperative pain” OR “postsurgical pain” AND “chronic” OR “persistent”. The present review focused on the incidence, pain development and chronification, and predisposing factors. It also discusses prevention, diagnosis, and treatment of chronic postoperative pain. Awareness of occurrence of chronic postoperative pain and recognizing risk factors is crucial for the day-to-day practice of the anesthesiologist. Hence, numerous surgical patients can have their outcome improved by preventing chronic postoperative pain, a condition scarcely identified and without a well-established treatment.
Keywords: Prevention of diseases; Postoperative pain; Chronic pain; Review